Fish meals - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Moussa Pouye, a farmer in DeDialocoto, near Tambacounda in Senegal, informs us: 'Fish is not only used for preparing our national dish thiébou diène, but also for producing milk and compost. After the women smoke the fish, they remove the head,...